U Urgensi Meneguhkan Eksistensi Bahasa Arab Dalam Kurikulum Pendidikan Nasional - Ahmad Bukhari Muslim; Rodhy Harisca (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
The objectives of this article is to identify the urgency of enhancing learning arabic inside national education curriculum in Indonesia. The urgency of this research is to conduct the development of teaching Arabic. The article adopted the qualitative descriptive method as the research designed the urgency of enhancing learning arabic inside national education curriculum. Data were analyzed by applying the four steps of Creswell's version collecting data, grouping, selecting, then interpreting the data and the data source was a documents review. The article findings indicated that learning arabic has a strategic position inside national education curriculum, as discussing about the urgency of enhancing learning arabic inside national education curriculum. Based on the research findings, the authors recommended the existence of Arabic inside national education curriculum should be strengthened and developed.